Empirical Study of E-Learning on Financial Literacy and Lifestyle: A Millenial Urban Generations Cased Study - Muhamad Ferdy Firmansyah; Haikal Zulian Maulana (Master Program of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
Technological developments have an influence on education, one of which is the development of online learning or more commonly known as e-learning. Technological developments in e-learning have long developed but significant developments occurred during the current Covid-19 pandemic where the education sector carried out online learning. This causes the existence of e-learning in both formal and non-formal education to be an important factor in the success of educational attainment. People in this era of globalization still have inconsistent attitudes in financial management individually, this causes the financial literacy of each individual to be different. This difference in financial literacy is one of the factors caused by different lifestyles. This study aims to see patterns of financial literacy in the development of e-learning where access to financial literacy learning is more developed in online channels. In addition to assumptions in financial literacy that are currently starting to develop online, this study also aims to determine the extent to which lifestyle will affect financial literacy. This study uses primary data and quantitative research methods approach using Confirmatory Factor Analysis (CFA). The results show that in e-learning, financial literacy is currently running and lifestyle has a significant effect on financial literacy. One of these lifestyle changes is the existence of E-Learning which shifts the lifestyle pattern of face-to-face learning to online learning. This can provide novelty in educational technology in the application of E-learning, especially in the case of financial literacy. In addition, e-learning can still support the achievement of education in financial literacy. Repair and improvement of e-learning facilities as the main learning media must be carried out. It is hoped that with this research, e-learning can be used in financial literacy learning, both through formal and non-formal education in the community and public web seminars during the Covid-19 pandemic.